Gamification elements in E-library services in higher education: A systematic review - Adedokun, Folashade Oyinlola (Springer Science and Business Media Deutschland GmbH, 2022)
E-libraries in higher education is to support teaching, learning, and research. Various services like online library services, e-reference services, e-SDI, and bibliographic services are rendered in the library to meet the users’ information, education, and research needs. E-libraries in institutions of higher learning play vital roles, such as the provision of metadata to access e-resources and the introduction of plagiarism software into the course management system to promote good practice. Despite the relevance of the e-library services, the library management experiences low patronage by the prospective users. As a result, of not being aware of the e-library services within the academic community, the academic performance of the potential users is affected negatively. Based on this, there is a need to adopt gamification in e-library services in higher education to promote library services and improve the academic performance of library users. Gamification is an act of using game elements to engage and motivate learners in non-game contexts. The study aims to explore various game elements used in e-library services. Therefore, this study explores the Scopus database to identify, extract, and analyze various game elements used in e-library services. Articles were selected using PRISMA Statement for inclusion and exclusion criteria. Out of the 41 articles extracted, 29 were thoroughly read and analyzed. In addition, the study results show that rewards, points, feedback, badges, leaderboards, and prizes are significant elements used in e-library services to bring fun, engagement, and enthusiasm. This study will guide the library management in providing necessary facilities that will aid in the implementation of gamification in e-library services in higher education. Lastly, the study suggests future research.